1998
DOI: 10.1016/s0096-3003(97)10062-5
|View full text |Cite
|
Sign up to set email alerts
|

A data-fitting procedure for chaotic time series

Abstract: DECLAIMER DISCLAIMERPortions of this document may be illegible in electronic image products. Images are produced from the best available original document. AbstractIn this paper we introduce data characterizations for fitting chaotic data to linear combinations of one-dimensional maps (say, of the unit interval) for use in subgrid-scale turbulence models. We test the efficacy of these characterizations on data generated by a chaotically-forced Burgers' equation and demonstrate, very satisfactory results in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…We will briefly discuss the procedures successfully used for model problem data in [12] now applied to the experimental data sets shown in Fig. 2(a-c).…”
Section: Data-fitting Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…We will briefly discuss the procedures successfully used for model problem data in [12] now applied to the experimental data sets shown in Fig. 2(a-c).…”
Section: Data-fitting Criteriamentioning
confidence: 99%
“…We discuss each of these briefly in what follows and provide specific formulas used in our analyses. More details can be found in [12].…”
Section: Data-fitting Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Gollub and Benson [9]), and in many cases the corresponding time series are physically realistic. In fact, McDonough et al [10] and Mukerji et al [11] have demonstrated the ability to model both numerical simulations and experimental data with linear combinations of a slight modiÿcation of (1). This raises the question of whether algebraic expressions such as Equations (3) might be of value for producing practical, computational models of turbulence, e.g.…”
Section: Introductionmentioning
confidence: 99%